2008
DOI: 10.1007/s12160-008-9068-1
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is Associated with Worse Mood on Stressful Days: Results from a National Diary Study

Abstract: Background Many smokers report smoking because it helps them modulate their negative affect (NA). The stress induction model of smoking suggests, however, that smoking causes stress and concomitant NA. Empirical support for the stress induction model has primarily derived from retrospective reports and experimental manipulations with non-representative samples of smokers. Moreover, prior studies have typically not considered contextual factors (e.g., daily stressors) that may impact the smoking-NA relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 112 publications
0
29
0
Order By: Relevance
“…Smokers commonly report smoking because it helps them to regulate their mood and to mitigate negative affect when confronted with stressors [19,41]. In contrast to both of these models, the stress induction model of smoking proposes that smoking actually causes stress and negative affect [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers commonly report smoking because it helps them to regulate their mood and to mitigate negative affect when confronted with stressors [19,41]. In contrast to both of these models, the stress induction model of smoking proposes that smoking actually causes stress and negative affect [41].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to both of these models, the stress induction model of smoking proposes that smoking actually causes stress and negative affect [41]. To address this possibility, we performed a sensitivity analysis to examine whether our findings were maintained following adjustment for negative affect, since negative affect could theoretically function as a mediator of the relationship between stress and smoking or a confounder of this association.…”
Section: Discussionmentioning
confidence: 99%
“…The permanent state of systemic inflammation and/or the chronic hypoxia that are hallmarks of COPD may explain the elevated rate of mood disorders in the COPD population (see details in Decramer et al, 2008). Another theory states that smoking may provoke mood disturbances in smokers because of the appearances of acute NIC deprivation periods several times a day, and -in consonance with this -several studies found that smoking cessation is associated with decreased levels of stress and anxiety in the long run (Parrott, 2006;Aronson et al, 2008). A recent investigation by Aronson et al (2008) has strengthened this theory, as the authors found -in contrast to the experiences of smokers -that heavy smoking is associated with greater negative affects, and this association is more pronounced on stressful days (Aronson et al, 2008).…”
Section: Explaining Theories Of Elevated Smoking Rates Among Patientsmentioning
confidence: 95%
“…Indeed, stress and negative affect may promote self-administration of nicotine, even in the absence of true emotion-modulating effects (Kassel, Stroud, & Paronis, 2003). In a seminal review of smoking, stress, and negative affect, Kassel et al (2003) concluded that tobacco-dependent smokers consistently endorse increased smoking in response to self-reported stress and negative affect (e.g., Aronson, Almeida, Stawski, Klein, & Kozlowski, 2008; Creson, Schmitz, & Arnoutovic, 1996; Hellerstedt & Jeffery, 1997; Steptoe, Wardle, Pollard, Canaan, & Davies, 1996), and that various manifestations of negative affect often precede smoking lapses and relapse to regular smoking among those attempting to quit (e.g., Brandon, Tiffany, Obremski, & Baker, 1990; Cummings, Jaen, & Giovino, 1985; Shiffman, 1982). The results of data collected in naturalistic settings corroborate these findings, with perceived stress shown to trigger smoking urges/cigarette consumption (Todd, 2004), and smoking lapses among recent quitters (Shiffman, Paty, Gnys, Kassel, & Hickcox, 1996).…”
Section: Effects Of Pain On Smokingmentioning
confidence: 99%